2013
DOI: 10.7314/apjcp.2013.14.1.499
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Serum Trace Elements in Renal Cell Carcinoma Cases

Abstract: Trace elements which are essential components of biological structures may also be toxic when present at levels above the amounts required for biological function. In our study, trace element levels were measured with furnace atomic absorption spectrophotometry in 33 newly diagnosed renal cell carcinoma cases (preoperative) and 32 healthy controls. When compared with the control group, it was found that the levels of cadmium (Cd), lead (Pb) were higher and the levels of zinc (Zn), iron (Fe) and manganese (Mn) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Zinc has a protective effect against free-radical injury (Wu et al, 2004). In previous studies, it has been reported that serum Zn concentrations were decreased in patients with ovarian, cervical, bladder and renal cancer (Cunzhi et al, 2003;Yaman et al, 2007;Pirincci et al, 2013). It is known that Zn concentration is significantly higher in prostate gland when compared to other tissues in human body (Costello et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc has a protective effect against free-radical injury (Wu et al, 2004). In previous studies, it has been reported that serum Zn concentrations were decreased in patients with ovarian, cervical, bladder and renal cancer (Cunzhi et al, 2003;Yaman et al, 2007;Pirincci et al, 2013). It is known that Zn concentration is significantly higher in prostate gland when compared to other tissues in human body (Costello et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be suggested that decreased serum Mn concentrations with disturbance of antioxidant mechanism can make target organs susceptible to carcinogens. Decreased serum Mn concentrations were reported in patients with bladder and renal cancers Pirincci et al;. It was shown that decreased Mn is potentially associated with decreased activity of superoxide dismutase in advanced stages of cancer (Gleason grade 3 or 4) when compared to group with Gleason 2 grade disease (Banas et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was discovered by a literature on kidney cancer patients that Cd level was higher than those of healthy people [9]. A study on colon cancer revealed that Cd level was higher than those of healthy people [10] It was presented by a study in Turkey that Cd level in renal cell carcinoma increased significantly compared to healthy people [16]. A study compared Cd levels of glioma cancer patients and healthy people and presented that CD level in glioma patients was significantly higher [17].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a research discovered that Pb level in kidney cancer patients was higher than those of healthy people [9]. It was presented by a study in Turkey that Pb level in renal cell carcinoma increased significantly compared to healthy people [16]. A literature on colon cancer found out that Pb level was higher than those of healthy people [10].…”
Section: Discussionmentioning
confidence: 99%
“…Trace elements which are important components of biological structures may also be toxic at levels above the amounts required for biological function (Pirincci et al, 2013). Currently, some trace elements have begun to gain attention in terms of the treatment and diagnosis of stroke since they are essential for sustaining metabolism of neurons and glia (Zangieva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%